2014
DOI: 10.1108/jic-06-2013-0064
|View full text |Cite
|
Sign up to set email alerts
|

Personal welfare and intellectual capital: the case of football coaches

Abstract: Purpose – The purpose of this paper is to present a framework that helps to analyze the dependence between personal welfare and individual (personal) intellectual capital (IIC). The authors also introduce the system of proxy indicator for personal intellectual capital (IC) of football coaches. Design/methodology/approach – This paper employs the idea that personal welfare depends on personal IC, particularly, talent. That is why initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Their value creation process is based on the interaction of their knowledge assets (e.g., professional football players as human capital; club branding as image, reputation, and relational capital; information and communication technology as structural capital), and to achieve their objectives, these resources have to be combined efficiently. Football players represent the human capital in KIOs (Lardo et al, 2017; Lombardi et al, 2020; Tomé et al, 2014) and the factor that mainly affects the final result. Due to the sector characteristics, we assumed the temporary or permanent contractual horizon or timing by workers as the duration of the contract.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their value creation process is based on the interaction of their knowledge assets (e.g., professional football players as human capital; club branding as image, reputation, and relational capital; information and communication technology as structural capital), and to achieve their objectives, these resources have to be combined efficiently. Football players represent the human capital in KIOs (Lardo et al, 2017; Lombardi et al, 2020; Tomé et al, 2014) and the factor that mainly affects the final result. Due to the sector characteristics, we assumed the temporary or permanent contractual horizon or timing by workers as the duration of the contract.…”
Section: Methodsmentioning
confidence: 99%
“…Football players represent the human capital in KIOs (Lardo et al, 2017;Lombardi et al, 2020;Tomé et al, 2014) and the factor that mainly affects the final result. Due to the sector characteristics, we assumed the temporary or permanent contractual horizon or timing by workers as the duration of the contract.…”
Section: Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…They also revealed that for evaluating a coach, the following points shouold be considered: the difference of the status of the team in the national league during the year, the status of the team in the competition table during the year, his image in the media, his personal history, being a former footballer, having sports activity in the team currently coaching, the championships won with the present team in previous years, the quality of the team's play, and the age of the individual. Additionally, the paper states that the most important factor affecting the price of coaches is nothing but their communication capital (19).…”
Section: Introductionmentioning
confidence: 99%
“…Footballers represent the human capital in this type of enterprise (Tomé et al, 2014;Lardo et al, 2017), and, from this perspective, there are very few studies on management strategies that are based on conscious and/or unconscious discrimination on the part of professional football clubs in the pursuit of their aims, such as increase attendance, profitability, and chances of winning.…”
Section: Introductionmentioning
confidence: 99%